Iraq : Considerations on Intergovernmental Fiscal Relations for the Constituent Assembly. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
In preparing for the discussions of the Iraqi Constituent Assembly, IMF and World Bank staff and consultant experts presented to senior officials from the central and local governments in Iraq, including from Kurdistan, key options that might be relevant for the discussions. This paper reflects the thrust of the discussions, including the views on the options prepared by the Iraqi officials, and develops a short-term work plan for the benefit of the assembly.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet